2015
DOI: 10.1186/s12882-015-0165-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between human leucocyte antigen subtypes and risk of end stage renal disease in Taiwanese: a retrospective study

Abstract: BackgroundEnd stage renal disease (ESRD) is prevalent in Taiwan. Human leukocyte antigens (HLA) have been found to be associated with the pathogenesis of autoimmune diseases, allergies and inflammatory bowel diseases, and there are emerging evidences of correlations between HLA genotypes and renal diseases such as diabetic nephropathy, IgA nephropathy, and glomerulonephritis. The aim of this study is to investigate detailed HLA subtypes in a case-control study of Taiwanese individuals.MethodsThe polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
4
14
1
Order By: Relevance
“…Several reports have examined possible associations between HLA types and ESRD 182,183,184 . Most of these studies have studied waitlisted candidates for renal transplantation in fairly homogeneous ethnic populations.…”
Section: Hla and Disease-independent Risk Of Esrdmentioning
confidence: 99%
“…Several reports have examined possible associations between HLA types and ESRD 182,183,184 . Most of these studies have studied waitlisted candidates for renal transplantation in fairly homogeneous ethnic populations.…”
Section: Hla and Disease-independent Risk Of Esrdmentioning
confidence: 99%
“…[7,8] Several emerging studies have described significant correlations between HLA and some renal diseases such as diabetic nephropathy, IgA nephropathy, and glomerulonephritis. [9,10] However, specific HLA types associated with ESRD have not been well documented. In this study, we aimed to show GHLA distribution in our region and the frequency of HLA allels in patients with chronic renal disease.…”
mentioning
confidence: 99%
“…HLA-DRB1*03 has been found to be protective against IgA nephropathy in European people 19 ; this study found that DRB1*03:01 was linked to increased renal function in Black African subjects. On the other hand, the same gene has been reported to be linked to increased risk of kidney dysfunction in Taiwanese, 20 Saudi Arabian, 21 Turkish, 13 and Brazilian 22 subjects. This study also found that HLA-DRB1*03:01 is linked to decreased kidney function in Indian subjects.…”
Section: Discussionmentioning
confidence: 98%